A randomised controlled trial of the effectiveness of self-weighing as a weight loss intervention. - Madigan, C; Jolly, K; Lewis, A; Aveyard, P; Daley, A (BioMed Central, 2014)
BACKGROUND: There is a need to find simple cost effective weight loss interventions that can be used in primary care. There is evidence that self-monitoring is an effective intervention for problem drinking and self-weighing might be an effective intervention for weight loss. PURPOSE: To examine the efficacy of daily self-weighing as an intervention for weight loss. METHODS: A randomised controlled trial of 183 obese adults, follow-up three months. The intervention group were given a set of weighing scales and instructed to weigh themselves daily and record their weight. Both groups received two weight loss consultations which were known to be ineffective. RESULTS: 92 participants were randomised to the intervention group and 91 to the control group. The intervention group lost 0.5 kg (95% CI 0.3 to 1.3 kg) more than the control group, but this was not significant. There was no evidence that self-weighing frequency was associated with more weight loss. CONCLUSIONS: As an intervention for weight loss, instruction to weigh daily is ineffective. Unlike other studies, there was no evidence that greater frequency of self-weighing is associated with greater weight loss. TRIAL REGISTRATION: ISRCTN05815264.